2020
DOI: 10.1111/jvim.15943
|View full text |Cite
|
Sign up to set email alerts
|

A de novo mutation in KRT5 in a crossbred calf with epidermolysis bullosa simplex

Abstract: A 6-day-old Belgian Blue-Holstein calf was referred because of a syndrome resembling epidermolysis bullosa simplex (EBS). The clinical phenotype included irregular and differently sized erosions and ulcerations spread over the body, in particular on the limbs and over bone prominences, as well as in the nasal planum and oral mucosa. Blisters were easily induced by rubbing the skin. The skin lesions displayed a clear dermal-epidermal separation at the level of the basal cell layer. Post mortem examination revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In contrast to humans, where more than 1000 variants in at least 16 genes have been associated with EB [1], molecular studies are rarely reported in domestic animals. EBS was associated with variants in PLEC in a litter of dogs [15], KRT5 in cattle [16,17] and a dog [18], and KRT14 in a cat [19]. DEB was associated with variants in COL7A1 in cattle [20] and dogs [21].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to humans, where more than 1000 variants in at least 16 genes have been associated with EB [1], molecular studies are rarely reported in domestic animals. EBS was associated with variants in PLEC in a litter of dogs [15], KRT5 in cattle [16,17] and a dog [18], and KRT14 in a cat [19]. DEB was associated with variants in COL7A1 in cattle [20] and dogs [21].…”
Section: Introductionmentioning
confidence: 99%